Departemen Periodonsia Fakultas Kedokteran Gigi Universitas Airlangga Surabaya, Indonesia - Chiquita Prahasanti (DiscoverSys Inc., 2014)
There were several mouth rinses in the market, but chlorhexidine, essential oil, triclosan-sodium fluoride mouth rinseshave often been used because of their effectivity of periodontal pathogen. They can inhibit plaque formation that theycan bind enamel surface coated pellicle. Thirty patients were recruited to the clinical of Periodontology Departmentand have several criterias: no systemic disease and no crowded of teeth. The patients divided of three groups; group Ipatients rinse with 0,2% chlorhexidine 15 ml, 1 minute; group II patients rinse with essential oil 15 ml, 1 minute; groupIII patients rinse with triclosan-sodium fluoride 15 ml, 1 minute. According to one way ANOVA test, there were nosignificant differences plaque index among of the three mouth rinses to prevent plaque formation. It was concluded thatusing chlorhexidine could inhibit the growth of plaque better essential oil and triclosan-sodium fluoride.